Antibacterial Activity of New [(2-Hydroxypropyl)-n-oximino]pyridines - SEN, NEJDET; KAR, YAKUP; KURBANOV, SULTAN; UYANIK, ARZU (Asian Journal of Chemistry, 2010)
The synthesized [(2-hydroxypropyl)-n-oximino]pyridine derivatives has been tested against the pathogenic four Grampositive bacteria Bacillus cereus (ATCC 11778), Staphylococcus aureus (ATCC 6538), Sarcina lutea (ATCC 9341) and Streptococs mutans (UCTC 10499) and three Gram-negative bacteria Salmonella typhimurium (1,4,5,12:;:1,2), Pseudomonas aeruginosa (ATCC 27853) and Escherichia coli (ATCC 29998). Generally, all synthesized compounds (IVa-c) showed strong activity compared to antibiotic drug (cefalexin). However, among this compounds (IVa) showed excellent activity against Bacillus cereus (ATCC 11778), Sarcina lutea (ATCC 9341), Salmonella typhimurium (1,4,5,12:;:1,2) and Escherichia coli (ATCC 29998) compared to cefalexin.